Survival of Lung Adenocarcinoma Patients with Tyrosine Kinase Inhibitor Therapy Based on EGFR Mutation Status in Tumor and Plasma Samples - Haryati, Haryati; Arganita, Fidya Rahmadhany; Oktaviyanti, Ika Kustiyah (http://dharmais.co.id/, 2023)
Background:The prognosis for epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) is greatly improved when treated with tyrosine kinase inhibitor (TKI). In this context, EGFR mutation status should be determined at the diagnosis stage but circulating tumor DNA (ctDNA) has been increasingly used for molecular profiling. Therefore, this study aimed to establish the correlation between the presence of ctDNA before TKI therapy and subsequent clinical outcomes Methods: A total of 18 patients with NSCLC who received EGFR-TKI therapy were enrolled. EGFR mutations were simultaneously identified in tumor samples and plasma ctDNA, as well as information regarding overall survival (OS) and progression-free survival (PFS). Result: These case studies showed that 14 of 18 patients (77.8%) with concordance results detected EGFR-positive mutations on ctDNA examination and histopathology from plasma and tumor samples, respectively. The median PFS was similar at 7.5 months in both groups, while the median OS was shorter in patients with EGFR-detected in ctDNA (17 vs. 25.5 months) after TKI-targeted therapy. Conclusion: The identification of EGFR mutations in plasma ctDNA was a promising, effective, and minimally invasive alternative to tumor biopsy. The existence potentially reflected the disease burden and showed a poor prognosis.